2010
DOI: 10.1111/j.1755-148x.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle inhibitor p21/ WAF1/ CIP1 as a cofactor of MITF expression in melanoma cells

Abstract: , a cyclin-dependent kinase inhibitor, may act as an antioncogene, but may also behave as a tumor promoting factor by inhibiting apoptosis. p21 is also a transcriptional regulator, exerting this activity independently of cyclin-dependent kinases. Increased p21 protein levels were found in a subset of melanomas. However, the mechanism(s) contributing to the tolerance of high p21 levels in melanoma help explain the tolerance of increased p21 levels found in some melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…] see Dotto, 2000;Perkins, 2002;Chen et al, 2009). p21 has been described to act both as a repressor and as a coactivator of the expression of genes (Poole et al, 2004;Fritah et al, 2005;Sestáková et al, 2010). Thus, the transcription function of p21 could be conserved in its Arabidopsis homolog KRP5 and provide a molecular link between the onset of endoreduplication and cell growth or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…] see Dotto, 2000;Perkins, 2002;Chen et al, 2009). p21 has been described to act both as a repressor and as a coactivator of the expression of genes (Poole et al, 2004;Fritah et al, 2005;Sestáková et al, 2010). Thus, the transcription function of p21 could be conserved in its Arabidopsis homolog KRP5 and provide a molecular link between the onset of endoreduplication and cell growth or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signalling pathways converge on the MITF-M specific promoter that harbours binding sites for PAX3, SOX10, CREB, FOXD3, LEF-1 and BRN2 among other transcription factors (Yokoyama & Fisher, 2011; Levy, Khaled & Fisher, 2006). Additionally, the MITF target gene CDKN1A/P21 has been shown to act as reciprocal transcriptional cofactor independently of its CDK inhibitor function, suggesting the existence of at least one positive feedback loop (Sestáková, Ondrusová & Vachtenheim, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In this way, this study also developed a predictor model for survival identifying a group of patients with shorter overall survival associated with VGP melanoma, which was related to the absence of p16 INK4a   or the presence of BCL6 protein expression in conjunction with either high Ki-67 expression or positive p21 CIP1   [22]. Although apparently paradoxical because of its cyclin-dependent inhibitory and tumor suppressor activities, a recent study reported that p21 CIP1 may also act as a tumor promoting factor by inhibiting apoptosis [23]. …”
Section: The Key Role Of Biomarkers In Melanoma Classification Refmentioning
confidence: 99%